Aglycone Polyether Nanchangmycin and Its Homologues Exhibit Apoptotic and Antiproliferative Activities against Cancer Stem Cells - Huang, Minjian (ACS Pharmacol Transl Sci, 2018)
[Image: see text] The potential of the polyether salinomycin as an inhibitory agent against cancer stem cells has attracted interest in this family of compounds. In this study, we found that the aglycone polyether nanchangmycin and its homologues show promising activities against breast cancer stem cells as well as 38 other different types of cancer cells by in vitro assays. We found that aglycone polyethers caused elevations in calcium levels, an accumulation of reactive oxygen species and mitochondrial inner membrane permeability to H(+) and K(+), resulting in the release of cytochrome c and apoptosis-inducing factor and the triggering of caspase-dependent apoptosis. Our analyses also indicate that aglycone polyethers are potent Wnt/β-catenin signaling inhibitors, blocking the Wnt pathway and resulting in reduced cell survival. Notably, the key autophagy-related proteins LC3A/B were also activated by aglycone polyether treatment. Furthermore, nanchangmycin showed inhibitory effects toward somatic tumors developed from MCF-7 paclitaxel-resistant breast cancer cells injected into BALB/c mice. Our study not only provides promising candidates for therapy against cancer stem cells but also provides the groundwork for identifying stronger therapeutic agents among the natural polyether compounds.